2003
DOI: 10.1046/j.1442-200x.2003.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening for renal and urinary tract anomalies in healthy infants

Abstract: Ultrasonograpy was effective for early detection of renal and urinary tract anomalies. Ultrasound screening in early infancy may permit early treatment, that can prevent renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
3
21
2
Order By: Relevance
“…For diagnostic purposes, it has been demonstrated that prenatal sonography is less sensitive than postnatal sonography [6,7], but to date only few studies have reported neonatal screening [2][3][4][5]. To the best of our knowledge, no study has explored the natural course of RPD detected during postnatal screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For diagnostic purposes, it has been demonstrated that prenatal sonography is less sensitive than postnatal sonography [6,7], but to date only few studies have reported neonatal screening [2][3][4][5]. To the best of our knowledge, no study has explored the natural course of RPD detected during postnatal screening.…”
Section: Introductionmentioning
confidence: 99%
“…The most common abnormality found in pre-or postnatal sonographic screening for congenital kidney and urinary tract anomalies (CAKUT) is collecting system dilatation, which may involve the renal pelvis (RPD) and/or the ureter [1][2][3][4][5][6]. The exact clinical significance that can be attributed to isolated (without calyceal involvement) RPD is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Data summarized from a questionnaire sent to the members of The Study Group of Ultrasonographic Screening for Congenital Anomalies of the Kidney and Urinary Tract in Japan indicated that the screening cost per child would be ¥1,200 ($US15), and 3 potential dialysis patients would be found per 55,000 children. If dialysis in these 3 patients could be delayed for 3.7 years, screening would pay for itself [24]. We have estimated that ultrasound screening for CAKUT in Salento costs €15 ($US20) per child.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only a few studies [3][4][5][6] have explored the natural course of RPD detected during postnatal screening. In order to assess the clinical impact of isolated severe RPD and define the medical intervention required, we have performed a prospective study in which we determined the incidence of isolated RPD and its natural course during the first year of life, without prophylactic antibiotic therapy (PAT) in a cohort of 2-month-old healthy infants who were screened by US for congenital kidney and urinary tract anomalies (CAKUT).…”
Section: Introductionmentioning
confidence: 99%
“…Collecting system dilatation of the renal pelvis and/or of the ureter are the most common abnormal findings in the urinary tract (1-5%) on prenatal/postnatal screening with ultrasound (US) [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%